Evaluasi implementasi program rumah keluarga sekar kasih dalam perbaikan status gizi di Wilayah Kerja Puskesmas Sekaran - Syifa Salsa Bila; Mardiana Mardiana (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Rumah Keluarga Sekar Kasih has completed the care of 8 toddlers from March 3, 2023, to September 1, 2023. After three months of completion of care, assistance was carried out. It was found that the nutritional status of toddlers based on WAZ was 37.5% underweight and 62.5% normal weight, according to HAZ as much as 62.5% stunting and 37.5% normal, and according to WHZ found 12.5% wasting and 87.5% normal.Objectives: The purpose of this study was to evaluate the implementation of the Rumah Keluarga Sekar Kasih program in improving nutritional status in the Sekaran Public Health Centre.Methods: This type of research is qualitative evaluation research with the CIPP method (context, input, process, product). Sampling by purposive sampling and snowball sampling, with a total of 12 informants. Data were collected through in-depth interviews, participatory observation, documentation, and literature study. The study was conducted in March 2024 in the Sekaran Public Health Centre.Results: The study results indicate that the program implementation has been generally successful, but there are areas that could be improved. These include limited supporting facilities, closed attitudes of some toddlers' families, and a lack of training for program implementers. The program's achievements from March 3, 2023, to March 3, 2024, include 13 toddlers completing treatment. Most underweight toddlers (76.9%) improved their nutritional status, while all toddlers with wasting improved nutrition, and the nutritional status of stunting toddlers did not show significant improvement.Conclusion: This study concludes that the Rumah Keluarga Sekar Kasih program needs improvement.